The Existence of A Norm Regarding The Execution of Fiduciary Guarantees After The Issuance of The Constitutional Court Decision Number 18/PUU/XVII/2019 - Rosyidi Hamzah; Fadhel Arjuna Adinda (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
The issuance of the decision of the Constitutional Court Number 18/PUU-XVII/2019 on January 6, 2020, caused a change in the execution pattern of Fiduciary Guarantee objects. The issuance of this Constitutional Court decision was not accompanied by creating a new norm regarding the execution pattern of Fiduciary Guarantee objects. It brings legal uncertainty and ambiguity in executing Fiduciary Guarantee objects. Therefore, the statements of the problem in this paper are how is the pattern of execution after the issuance of the Constitutional Court Decision Number 18/PUU-XVII/2019? And how is the existence of new norms after the Constitutional Court Decision Number 18/PUU-XVII/2019? The research method used is the normative legal research method. The pattern of execution of Fiduciary Guarantee objects after the issuance of the Constitutional Court Decision Number 18/PUU-XVII/2019 experienced ambiguity and obscurity because the contents of the Constitutional Court’s decision were only general norms. The existence of new norms after the Constitutional Court Decision Number 18/PUU-XVII/2019 is necessary to support legal certainty in executing objects of Fiduciary Guarantee.